Association between surgical volume and clinical outcomes following coronary artery bypass grafting in contemporary practice. Issue 10 (7th August 2019) - Alkhouli, Mohamad; Alqahtani, Fahad; Cook, Chris C.
Abstract: Background: Studies assessing the association between surgical volume and coronary artery bypass grafting (CABG) outcomes yielded conflicting results. Given the substantial recent decrease in CABG volume, we sough to examine the volume‐outcomes effect in contemporary practice. Methods: The National Readmission Database was queried to identify patients undergoing CABG between January 1, 2015 and December 31, 2016. Risk‐adjusted in‐hospital morbidity, mortality, length‐of‐stay, cost, and 30‐day readmission were compared between low‐, intermediate‐, and high‐volume centers. Results: A total of 411 159 CABG hospitalizations at 1558 hospitals were included. Hospitals were classified into three tertiles (high > 250, intermediate 100‐250, and low‐volume < 100). Hospitals in the highest tertile (n = 568) performed 73.9% of all CABG operations, while those in the intermediate (n = 452), and low (n = 538) volume tertiles performed only 21.7% and 4.4% of all CABGs, respectively. The median number of CABGs performed at high‐, intermediate‐, and low‐volume hospitals was 45 316 335, respectively. After risk adjustment, undergoing CABG at low‐ or intermediate‐ volume hospital (vs high‐volume hospitals) was associated with higher in‐hospital death (odd ratio [OR] = 1.31, 95% confidence interval [CI], 1.19‐1.44, and OR = 1.11, 95% CI, 1.05‐1.17, respectively, P  < .001). Similarly, adjusted odds of stroke, acute kidney injury, and blood transfusion were higher at low‐ and intermediate‐volume centers compared with high‐volume centers. Undergoing CABG at a low‐volume center was associated with 50% higher adjusted cost and 77% higher adjusted 30‐day readmissions. Conclusions: In contemporary practice, in which one‐third of CABG‐capable hospitals perform < 100 CABG operations annually, a strong relationship is observed between surgical volume and adjusted in‐hospital morbidity, mortality, cost, and 30‐day readmission.